Analisis Kemampuan Literasi Matematis Siswa SMA 2 Makassar Pada Soal PISA Level 5 - Andi Cahaya Rezky Andini; Andi Trisno Trisno; Abdul Rahman; Bernard Bernard (FKIP Universitas Mataram, 2026)
This study aims to analyse the mathematical literacy skills of students at Makassar State Senior High School 2 in solving Programme for International Student Assessment (PISA) Level 5 questions, as well as to identify the types of errors and thinking strategies that arise during the solving process. This study was motivated by the low mathematical literacy scores of Indonesian students in the PISA study (OECD, 2021), particularly in the context of highly complex questions that require reflective reasoning and non-routine problem-solving skills. This study used a descriptive qualitative approach with a case study design. The research subjects consisted of 32 Grade XI students from Makassar State Senior High School 2 who were selected purposively. The research instruments were a PISA Level 5-based mathematical literacy test and interview guidelines to identify students' thinking processes. Data analysis was conducted through the stages of reduction, presentation, and conclusion drawing based on the Miles and Huberman model, as well as referring to the mathematical literacy framework. Which includes the abilities to formulate, employ, and interpret. The results of the study indicate that most students are still at an intermediate level (Levels 3–4) with a predominance of conceptual and representational errors, particularly in understanding the relationships between variables and converting verbal information into mathematical models. Students with high abilities (such as Banapati Maulana) were able to demonstrate reflective and argumentative thinking processes that reflected Level 5 characteristics, while students with moderate (such as Aura Agni) and low (such as Siti Fatimah) abilities tended to stop at the procedural stage without contextual reflection. These findings confirm that improving students' mathematical literacy requires not only mastery of concepts and procedures, but also practice in reflective, argumentative, and contextual thinking through problem-based and literacy-based learning approaches.